Discoid lupus erythematosus - Anilkumar L Bhoweer; Sudarshan G Ranpise (Wolters Kluwer Medknow Publications, 2018)
Oral ulcerative lesions are very common and a proper diagnosis is required of the nonresponsive lesions to common antiseptic and analgesic creams which do not work on those ulcers. Specific local potent steroids work faster with given soft trays to apply, which holds the medicine for local action, as it does not get washed away with the mouth saliva. Lupus Erythematosus lesions respond slowly with medicine as this is an autoimmune disease. Systemic lupus erythematosus, it occurs, is a cutaneous autoimmune disease and can affect the skin and various internal organs. Thus, proper observation of oral ulcers is important and if there are any indications of such skin infections, then it requires a Dermatologist to handle for life-saving management as the disease is sometimes fatal. A general warning signal of recurrence can help the patient with history of oral lesion for the proper management even later in life by a Dermatologist. Oral lesions are very important in diagnosing systemic disease in many cases. Oral lesions are thus the mirror of general health.